2004
DOI: 10.1016/j.jhealeco.2004.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the state children’s health insurance program on health insurance coverage

Abstract: This paper presents the first national estimates of the effects of the SCHIP expansions on insurance coverage. Using CPS data on insurance coverage during the years 1996-2000, we estimate instrumental variables regressions of insurance coverage. Our regression results imply that 9% of children meeting income eligibility standards for SCHIP gained public insurance. While low, our estimates indicate that states were more successful in enrolling children in SCHIP than they were with prior Medicaid expansions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(65 citation statements)
references
References 24 publications
1
62
0
Order By: Relevance
“…In a key early econometric study of crowd-out for child coverage, Cutler and Gruber (1996) found that up to 50% of the increase in Medicaid coverage for children in the early 1990s was offset by a decrease in private coverage. More recent studies have produced similar estimates while others found lower crowd-out estimates for the same Medicaid expansions and the later CHIP program (Gruber & Simon, 2008;Thorpe & Florence, 1998-1999LoSasso & Buchmueller, 2004;Shore-Sheppard 2008;Ham & Shore-Sheppard, 2005). Due to methodological limitations, most studies estimate a single substitution value nationwide.…”
Section: E3mentioning
confidence: 90%
See 2 more Smart Citations
“…In a key early econometric study of crowd-out for child coverage, Cutler and Gruber (1996) found that up to 50% of the increase in Medicaid coverage for children in the early 1990s was offset by a decrease in private coverage. More recent studies have produced similar estimates while others found lower crowd-out estimates for the same Medicaid expansions and the later CHIP program (Gruber & Simon, 2008;Thorpe & Florence, 1998-1999LoSasso & Buchmueller, 2004;Shore-Sheppard 2008;Ham & Shore-Sheppard, 2005). Due to methodological limitations, most studies estimate a single substitution value nationwide.…”
Section: E3mentioning
confidence: 90%
“…In the first, econometric-based approaches are used to estimate the impact of Medicaid expansion on private insurance take-up (usually referred to as "crowd-out" studies). These studies use variations of Cutler and Gruber's original identification technique (Gruber & Simon, 2008;LoSasso & Buchmueller, 2004;Seiber & Florence, 2010;Shore-Sheppard, 2008). This econometric approach examines eligibility variation across states to produce national estimates for the magnitude of substitution, often through instrumental variable models designed to address the possible endogeneity of public insurance eligibility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent analysis has suggested varying estimates ranging from values similar to Cutler and Gruber to estimates that there is near zero crowd-out (Gruber & Simon, 2008). These studies primarily relied on three methods: an econometric instrumental variable (IV) approach (Cutler & Gruber, 1996;Lo Sasso & Buchmueller, 2004), comparing children who gained access to expanded Medicaid/CHIP programs to control groups that did not (Blumberg, Dubay, & Norton, 2000;Yazici & Kaestner, 2000), and estimates of substitution using surveys (Sommers, Zuckerman, Dubay, & Kenney, 2007), all of which have weaknesses (Seiber & Sahr, 2011).…”
Section: Past Workmentioning
confidence: 99%
“…Using a simulated eligibility design, Lo Sasso and Buchmueller (2004) found a marginal take-up rate for public insurance of 8.1%, and crowd-out rates between 18% and 50% depending on the exact specification used. A similar paper by Gruber and Simon (2008) largely confirmed these results, estimating a low take-up rate of 5.5% for public insurance accompanied by a direct crowd-out rate of 30%.…”
mentioning
confidence: 99%